Tecendo os fios da trajetória do cuiabano Silva Freire (1949-1991) : percurso histórico cultural das experiências no campo da leitura e da escrita do autor - Gabriel, Sheila Cristina Ferreira (2024)
This thesis addresses the trajectory of Cuiabano author Silva Freire and aimed to understand his constitution as a reader and author in the period from 1949 to 1991. And to achieve the objective, we highlighted some aspects of the network woven by Silva Freire and his relationship with Cuiabano threads (Cuiabá); we identified how the book and reading were brought together along the author’s path; and how his path as a writer took shape until he became an author. The research was conducted with the aim of answering the following question: how did Silva Freire establish himself as a reader, writer, until he became an author? The hypothesis that we consider valid is that Silva Freire's authorial trajectory was motivated by the desire to disseminate Cuiabá culture, beyond Cuiabá, and that his writing process was permeated by the glimpse of a possible recipient or potential reader of his work. And with this focus, he used several strategies, such as publishing poetry in local and national newspapers, distributing his texts to the population of Cuiabá, to promote access to his texts by different individuals in Brazilian society. Methodologically, we use the principles of Book History, using as sources the literature (poems, chronicles and stories) produced by Silva Freire, newspaper clippings, correspondence, speeches, which make up the collection of Casa Silva Freire, also using the sources oral information accessed through interviews. As an analysis method, we are guided by the precepts of discourse analysis, from the perspective of Mikhail Bakhtin, also dialoging with the concepts of reading and authorship, dialogism, literature, modernism, intensiveism, oral history, among others. The results indicate that: Silva Freire was an active agent in the local cultural scene and also in Rio de Janeiro, during the period he attended the Law course; there is no way to discuss Silva Freire without understanding his relationship with Cuiabá, which, for him, was the realization of a feeling that he called cuiabania; Silva Freire used the precepts of Intensivism throughout his authorial production; the author from Cuiabá was a mediator and agent of information, and, through his dissemination strategies, allowed his text to reach distant places, beyond Mato Grosso; Silva Freire's worldview, built from his practical and theoretical experiences, permeated his writing, which, from the beginning, had the reader as an essential concern. We hope that the results of the research will contribute to productions on the History of the Book in Mato Grosso, specifically, in Cuiabá.